McDonald & Dodds. Year one [videorecording (DVD)] - Gouveia, Tala; Watkins, Jason, 1966-; Murray, James, 1975- (BBC Archives, 2021)
Transferred to Bath from London and looking to make good, ambitious DCI Lauren McDonald (Tala Gouveia) found the first task handed her was to see if she couldn't gently nudge her new assistant--aging, colorless desk jockey DS Dodds (Jason Watkins)--into retirement. The mismatched pair would prove surprisingly able in cracking the hardest cases, in this clever ITV offering; James Murray, Jack Riddiford, Pearl Chanda also starred.